New species of Cymatodera Gray (Coleoptera: Cleridae: Tillinae) from México and Central America, with notes on others - Rifkind, Jacques (Zootaxa, 2015)
Nineteen new species of Cymatodera Gray are described: C. mexicana, C. cicatricula, C. matehualacaligoides, C. brailovskyi, C. durangoensis, C. monticola, C. paucipunctata, C. anulata, C. christina, C. copei, C. oxchuc, C. merickeli, C. romeroi, C. cellulosa, and C. acutipennis from México; C. doda from México, Nicaragua and Costa Rica; C. carinipennis from México and Guatemala; C. rileyi from México, Honduras, and Belize, and C. wilsoni from Costa Rica. These species are figured, along with the type of C. kolbei Schenkling, and a lectotype is designated for the latter. I include a brief discussion on the prevalence and evolution of brachyptery in Cymatodera.